2002
DOI: 10.1079/phn2001248
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in British vegetarians

Abstract: Objective: To compare the mortality of British vegetarians and non-vegetarians. Design: Analysis of original data from two prospective studies each including a large proportion of vegetarians -the Oxford Vegetarian Study and the Health Food Shoppers Study. Standardised mortality ratios (SMRs) compared with the population of England and Wales were calculated from deaths before age 90 for vegetarians and nonvegetarians in each study. Death rate ratios (DRRs) for vegetarians compared with nonvegetarians within ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 18 publications
4
60
0
1
Order By: Relevance
“…Nevertheless, the lack of statistical association may reflect the relative small number of cases. A previous analysis of mortality in this cohort (Appleby et al, 2002) showed similar death rates for colorectal cancer in vegetarians and non-vegetarians based on 25 and 24 deaths from colorectal cancer, respectively. However, in a prospective investigation of Seventhday Adventists (Singh and Fraser, 1998), cancer of the colon was significantly more common in non-vegetarians than in vegetarians.…”
Section: Discussionsupporting
confidence: 67%
“…Nevertheless, the lack of statistical association may reflect the relative small number of cases. A previous analysis of mortality in this cohort (Appleby et al, 2002) showed similar death rates for colorectal cancer in vegetarians and non-vegetarians based on 25 and 24 deaths from colorectal cancer, respectively. However, in a prospective investigation of Seventhday Adventists (Singh and Fraser, 1998), cancer of the colon was significantly more common in non-vegetarians than in vegetarians.…”
Section: Discussionsupporting
confidence: 67%
“…Risk factors for mortality from all causes, malignant neoplasms, circulatory diseases, and ischemic heart diseases All causes (n = 456) Malignant neoplasms (n = 107) Circulatory diseases (n = 219) Ischemic heart diseases (n = 60) Both subjects who avoided meat and fish and those who consumed moderate amounts of meat and/or fish experienced strongly reduced mortality, indicating that both groups are not representative of the general population. A similar 50% to 60% reduction in mortality has been reported for other vegetarian and health-conscious cohorts in Europe after a comparable length of follow-up time (5,11). Several nondietary factors that differ in their prevalence in our study population and in the general population could partly explain the low mortality.…”
Section: Discussionsupporting
confidence: 53%
“…Os estudos devem levar em consideração o fato de que os vegetarianos são geralmente mais magros que os indivíduos onívoros (Kennedy et al, 2001) e que os níveis pressóricos nas populações ocidentalizadas tendem a aumentar com o peso, uma vez que as diferenças no peso corporal de indivíduos vegetarianos e não vegetarianos pode ser um importante fator contribuinte para as diferenças de pressão arterial observadas entre esses grupos (Appleby et al, 2002). Outro fator a ser avaliado é o fato de que dietas vegetarianas apresentam menor densidade energética e maior conteúdo de fibras, embora os estudos observacionais e ensaios clínicos não tenham chegado a consenso sobre o efeito significativo das fibras nos níveis pressóricos (Burke et al, 2001;He & Whelton, 1999).…”
Section: Dietas Que Reduzem a Pressão Arterial Dieta Vegetarianaunclassified